Preparation method of anti-reflection glass, glass cover plate and terminal equipment

By forming a nano -grade film layer on the surface of the glass, using sodium silicate, ETDA sodium, and aluminum chloride hydrolyzed acid solution to solve the problem of high glass and low cost and limited modeling in existing technology, and achieve efficient efficiency. Increasing the effect of reducing reverse effects.

CN119371110AInactive Publication Date: 2025-01-28BEIJING XIAOMI MOBILE SOFTWARE CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202310932549.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the prior art realizes glass revelation and reduction, the cost is high and the shape is limited, making it difficult to meet the complex demand for cover glass by smart electronic products.

Method used

By immersing the pre -treated glass into the hydrolyzed acid solution containing sodium silicate, ETDA sodium, and aluminum chloride to form a nanocar film layer. The refractive index of the sparse interface can be achieved.

Benefits of technology

This method can effectively reduce the reflectivity of the glass, so that it will gradually change from the air to the glass, to achieve the effect of increasing the reducing reverse, and at the same time adapt to the glass of different shapes, avoiding high cost and limited modeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371110A_ABST
    Figure CN119371110A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of anti-reflection glass, a glass cover plate and terminal equipment. The preparation method comprises an etching step, pretreated glass is immersed in a hydrolysis acid solution containing sodium silicate, ETDA disodium and aluminum chloride, a nanoscale film layer is generated on the surface of the aluminum-silicon glass or soda-lime glass, and the film layer is provided with a plurality of nanoscale wedge-shaped structures with the wavelength smaller than that of visible light. The scheme can achieve the purpose of anti-reflection, and can adapt to glass of different shapes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of glass preparation, and in particular to a method for preparing anti-reflection and anti-transmittance glass, a glass cover plate and a terminal device. Background Art

[0002] The integration and complexity of current smart electronic products have entered a new and higher dimension. Among them, the demand for anti-reflection and anti-reflection of cover glass in display, camera and other sub-modules is becoming increasingly strong, but conventional dry PVD or wet coating has the problems of high cost and limited shape. Therefore, it is very important to find a glass anti-reflection solution with reliable performance and cost advantage. Summary of the invention

[0003] The present application provides a method for preparing anti-reflection and anti-reflection glass, a glass cover plate and a terminal device, which can achieve the purpose of anti-reflection and anti-reflection and can adapt to glass of different shapes.

[0004] A method for preparing anti-reflection and anti-transmission glass, comprising:

[0005] In the etching step, the pretreated glass is immersed in a hydrolyzed acid solution containing sodium silicate, disodium ETDA and aluminum chloride to generate a nano-scale film layer on the surface of the glass. The film layer has a plurality of nano-scale wedge-shaped structures smaller than the wavelength of visible light.

[0006] Optionally, the acidic solution contains 0.1-0.4 mol / L sodium silicate, 0.04-0.12 mol / L disodium EtDA, and 0.05-0.15 mol / L aluminum chloride.

[0007] Optionally, the film layer has a thickness of 150 nm to 250 nm.

[0008] Optionally, in the etching step, the temperature of the acid solution is first controlled at 80±5° C., and then the pretreated glass is immersed in the acid solution.

[0009] Optionally, the glass immersed in the acidic solution is vibrated with a vibration frequency of not less than 60 Hz.

[0010] Optionally, the glass immersed in the acidic solution generates periodic vibration in the form of a sine wave, and when the amplitude of the periodic vibration is less than 4 mm, the etching time is controlled to be greater than 50 min; when the amplitude of the periodic vibration is greater than 4 mm, the etching time is controlled to be less than 50 min.

[0011] Optionally, the pretreated glass is immersed in the acidic solution at a uniform speed of 18 cm / min to 20 cm / min.

[0012] Optionally, the preparation method further comprises a pretreatment step before the etching step:

[0013] Cleaning the glass using a glass cleaning agent; and

[0014] A 0.015vt% by volume hydrofluoric acid aqueous solution is used for corrosive cleaning.

[0015] Optionally, the preparation method further comprises a strengthening step arranged after the etching step:

[0016] The etched glass is immersed in a molten salt containing sodium and potassium.

[0017] Optionally, the preparation method further comprises a post-processing step after the strengthening step:

[0018] A hydrophobic layer of perfluorosilane is evaporated on the etched glass surface.

[0019] A glass cover plate, comprising:

[0020] the cover body; and

[0021] The nanometer-scale film layer is formed by etching the cover plate body.

[0022] Optionally, the pretreated glass is immersed in a hydrolytic acidic solution containing sodium silicate, disodium ETDA and aluminum chloride to generate a nanoscale film layer on the surface of the glass, wherein the film layer has a plurality of nanoscale protrusions smaller than the wavelength of visible light.

[0023] Optionally, the membrane layer is also provided with a hydrophobic layer.

[0024] A terminal device comprises the glass cover plate mentioned above.

[0025] The present application provides a method for preparing anti-reflection glass, a glass cover plate and a mobile terminal, wherein the protrusion structure on the film layer has a microscopic morphology characteristic of being pointed at the top and wide at the bottom, which can adjust the refractive index of the light-dense / light-sparse interface, reduce the refractive index difference of the interface, and make the refractive index of the interface change continuously from air to glass, thereby achieving the purpose of anti-reflection. In addition, the film layer is formed by the corrosion of the glass surface by an acidic solution, which is equivalent to the film layer growing into the glass body, and the preparation method can adapt to glass of different shapes. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a flow chart of a method for preparing anti-reflection and anti-reflection glass according to an exemplary embodiment of the present application;

[0027] Figure 2This is a schematic diagram of the top view and cross-sectional morphology of the glass surface after the sub-wavelength precision etching provided by the present application;

[0028] Figure 3 Another electron microscope schematic diagram of the top view and cross-sectional morphology of the glass surface after the sub-wavelength precision etching provided by the present application;

[0029] Figure 4 is the reflectivity of the single interface of the sample at different angles after etching. DETAILED DESCRIPTION

[0030] Here, exemplary embodiments will be described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application.

[0031] The terms used in this application are only for the purpose of describing specific embodiments, and are not intended to limit this application. Unless otherwise defined, the technical terms or scientific terms used in this application should be understood by people with ordinary skills in the field to which this application belongs. The "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, similar words such as "one" or "one" do not indicate quantity restrictions, but indicate that there is at least one, and will be separately described if only "one" is referred to. "Multiple" or "several" means two or more. Unless otherwise specified, similar words such as "front", "rear", "lower" and / or "upper", "top", "bottom" are only for the convenience of explanation, and are not limited to one position or one spatial orientation. Similar words such as "include" or "comprise" mean that the elements or objects appearing in front of "include" or "comprise" cover the elements or objects listed after "include" or "comprise" and their equivalents, and do not exclude other elements or objects. The words "connected" or "connected" and the like are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect.

[0032] At present, PVD (Physical Vapor Deposition) and wet coating can be used to achieve anti-reflection and anti-reflection of glass. The above two solutions use two transparent materials with high and low refractive indices (compared to glass) to construct a film system (such as SiO2 / Si3N4), and reduce the "equivalent refractive index" through interference, ultimately achieving the effect of anti-reflection. However, precisely because of interference, the above scheme requires the deposition of multiple layers, which makes the 3D-shaped glass appear different colors at the edges, and even flat sheets will have large-angle color cast problems. In addition, because the PVD film layer has stress problems, it will affect the preset stress of the chemically strengthened glass, causing the glass strength to decrease and break.

[0033] Based on this, the present application provides a method for preparing anti-reflection glass, which can form an anti-reflection film layer on the glass surface. The film layer is generated inward and is less affected by the shape of the glass.

[0034] Please refer to Figures 1 to 3 , Figure 1 The present invention is a flow chart of a method for preparing anti-reflection and anti-reflection glass according to an exemplary embodiment of the present application. Figure 2 This is a schematic diagram of the electron microscope showing the top view and cross-sectional morphology (reference wavelength is 550nm) of the glass surface after the sub-wavelength precision etching provided by the present application. Figure 3 Another electron microscope schematic diagram of the top view and cross-sectional morphology of the glass surface (reference wavelength is 550nm) after the sub-wavelength precision etching provided by the present application.

[0035] The present application provides a method for preparing anti-reflection and anti-transmission glass, and the preparation method includes an etching step S10.

[0036] In the etching step S10, the pretreated glass is immersed in a hydrolytic acid solution containing sodium silicate, disodium ETDA and aluminum chloride to generate a nano-scale film layer on the surface of the glass, and the film layer has a plurality of nano-scale protrusion structures smaller than the wavelength of visible light. The glass can be aluminosilicate glass or soda-lime glass. The protrusions include but are not limited to wedge-shaped protrusions and convex cone-shaped protrusions.

[0037] According to the above description, the wedge-shaped structure has a microscopic morphology of being pointed at the top and wide at the bottom, which can adjust the refractive index of the light-dense / light-sparse interface, reduce the refractive index difference of the interface, and make the refractive index of the interface change continuously from air to glass, thereby achieving the purpose of increasing transmittance and reducing reflection. In addition, the film layer is formed by the corrosion of the glass surface by an acidic solution, which is equivalent to the film layer growing into the glass body. The preparation method can be adapted to glass of different shapes, including but not limited to 3D glass or flat glass.

[0038] The main function of sodium silicate is to corrode the surface of aluminosilicate glass or soda-lime glass as the main component of acidic solution after hydrolysis. Disodium ETDA provides viscosity, and the reaction process will produce micelles of the third product, which will discretely adhere to the glass surface, hindering the reaction and making the glass surface present a wedge-shaped morphology. Aluminum chloride can be used as a buffer.

[0039] It should be noted that, in view of the different processing technologies of aluminosilicate glass or soda-lime glass, in addition to the main components of sodium silicate, disodium ETDA and aluminum chloride, the acidic solution may also include other chemical additives to improve the compatibility of the materials, which may be selected according to the actual processing technology. The processing technologies of aluminosilicate glass or soda-lime glass include but are not limited to float processing technology and overflow processing technology.

[0040] In one embodiment, the acidic solution contains 0.1-0.4 mol / L sodium silicate, 0.04-0.12 mol / L disodium ETDA and 0.05-0.15 mol / L aluminum chloride, which is beneficial to improving the etching effect. For example, sodium silicate can be set to 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L. Disodium ETDA can be set to 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L. Aluminum chloride can be set to 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.11 mol / L, 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, 0.15 mol / L, but is not limited thereto.

[0041] In one embodiment, the thickness of the film layer ranges from 150 nm to 250 nm, and can be 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, or 250 nm.

[0042] In one embodiment, in the etching step S10, the temperature of the acidic solution can be first controlled at 80±5°C, and then the pretreated aluminosilicate glass or soda-lime glass is immersed in the acidic solution, so that the etching temperature can be accurately controlled, which can not only avoid the film layer from being loose and the refractive index being lower than that of the glass body due to the etching temperature being too high, but also avoid the etching depth being insufficient and the refractive index of the film layer and the glass body being the same due to the etching temperature being too low. For example, the temperature of the acidic solution can be controlled at 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, but is not limited thereto.

[0043] In one embodiment, in the etching step S10, the aluminosilicate glass or soda-lime glass immersed in the acidic solution is vibrated, and the vibration frequency is not less than 60 Hz. For example, the aluminosilicate glass or soda-lime glass can be vibrated by a vibrator. In an actual processing scenario, the aluminosilicate glass or soda-lime glass can be placed in a rack, and the glass can be driven to vibrate by vibrating the rack. In this step, the vibration can shake off the precipitated by-products produced during the etching process, thereby improving the etching effect. Among them, the specific vibration form is not limited, including but not limited to periodic vibration in the form of a sine wave. The vibration frequency can be set to 60Hz, 70Hz, 80Hz, 90Hz, 100Hz, but is not limited to this.

[0044] In one embodiment, in the etching step S10, the etching time of the aluminosilicate glass or soda-lime glass can be controlled, for example, the etching time can be controlled within the range of 40 min to 60 min. In a specific embodiment, in the etching step S10, the aluminosilicate glass or soda-lime glass immersed in the acidic solution is made to generate periodic vibration in the form of a sine wave, and when the amplitude of the periodic vibration is less than 4 mm, the etching time is controlled to be greater than 50 min, for example, 60 min, but not limited thereto. When the amplitude of the periodic vibration is greater than 4 mm, the etching time is controlled to be less than 50 min, for example, 40 min, but not limited thereto.

[0045] In one embodiment, in the etching step S10, the pretreated aluminosilicate glass or soda-lime glass can be slowly immersed in the acidic solution to ensure the stability of the quality during the same batch of etching. For example, multiple pieces of glass can be slowly immersed in the acidic solution at the same time. In an optional embodiment, the pretreated aluminosilicate glass or soda-lime glass can be immersed in the acidic solution at a uniform speed of 18 cm / min to 20 cm / min. That is, the immersion speed can be 18 cm / min, 19 cm / min, 20 cm / min, but is not limited to this.

[0046] Since the film layer formed on the glass surface is of nanometer thickness, high requirements are imposed on the surface quality and cleanliness of the glass. In one embodiment, the preparation method further comprises a pretreatment step S05 before the etching step S10.

[0047] The preprocessing step S05 includes:

[0048] Cleaning the aluminosilicate glass or soda-lime glass using a glass cleaning agent; and

[0049] A 0.015vt% by volume hydrofluoric acid aqueous solution is used for corrosive cleaning.

[0050] In the pretreatment step S05, cleaning with a glass cleaning agent is conventional cleaning. The main component of the glass cleaning agent is a surfactant, which is slightly alkaline or neutral. Cleaning with hydrofluoric acid is corrosive cleaning. Hydrofluoric acid is a weak acid with extremely strong corrosiveness. It can strongly corrode metals, glass and silicon-containing objects, so that pinholes on the glass itself or surface adhesion dirt can be removed. In some embodiments, preliminary cleaning with a glass cleaning agent can be performed first, and then corrosive cleaning can be performed with hydrofluoric acid.

[0051] In one embodiment, the preparation method further includes a strengthening step S20 after the etching step.

[0052] The strengthening step S20 includes: immersing the etched aluminosilicate glass or soda-lime glass in a molten salt containing sodium and potassium. In this step, potassium ions enter the glass surface and displace the sodium ions in the glass, and potassium ions replace the sodium ions. Since the radius of potassium ions is larger than the radius of sodium ions, the density of the glass surface is increased, and compressive stress is generated on the glass surface, thereby achieving a strengthening effect. It should be noted that the strengthening step S20 can be repeatedly implemented, thereby strengthening the glass surface multiple times.

[0053] In one embodiment, the preparation method further includes a cleaning step, which is arranged after the strengthening step S20, and cleans the strengthened aluminosilicate glass or soda-lime glass, including but not limited to cleaning with an alkaline or neutral cleaning agent.

[0054] In one embodiment, the preparation method further includes a post-processing step S30 provided after the strengthening step S20.

[0055] The post-processing step S30 includes: evaporating a hydrophobic layer of perfluorosilane on the surface of the etched aluminosilicate glass or soda-lime glass. The hydrophobic layer serves as a water-repellent protective layer with low surface energy, which reduces the possibility of hydrolysis between the glass and water vapor in the atmosphere, avoids deterioration of the glass strength, and improves the durability of use.

[0056] Please refer to Figure 4 , Figure 4 is the reflectivity of the single interface of the sample at different angles after etching.

[0057] Depend on Figure 4 It can be seen that the three curves close to the horizontal axis are the reflectivity of glass at different angles under the sub-wavelength precision etching process provided by the present application. At different incident angles, the corresponding reflectivity of the reference wavelength of 550nm is less than 1%, and the anti-reflection and anti-transmission effect is significant.

[0058] Table 1 is a comparison table of the advantages and disadvantages of the glass preparation method provided in this application and etching AG and PVD.

[0059] Table 1

[0060]

[0061]

[0062] The present application also provides a glass cover plate, the glass cover plate comprising a cover plate body and a nano-scale film layer formed on the surface of the cover plate body, the film layer being formed by etching the cover plate body. The application scenarios of the glass cover plate are not limited. In one embodiment, the cover plate body may be etched by a hydrolytic acidic solution containing sodium silicate, disodium LETDA, and aluminum chloride to form the film layer.

[0063] Specifically, the etching process is: immersing the pretreated glass in a hydrolyzed acidic solution containing sodium silicate, disodium ETDA and aluminum chloride, generating a nanoscale film layer on the surface of the glass, and the film layer has a number of nanoscale protrusions smaller than the wavelength of visible light. The protrusions have a microscopic morphology of being pointed at the top and wide at the bottom, which can adjust the refractive index of the light-dense / light-sparse interface, reduce the refractive index difference of the interface, and make the refractive index of the interface change continuously from air to glass, thereby achieving the purpose of increasing transmittance and reducing reflection. In addition, the film layer is formed by the corrosion of the glass surface by an acidic solution, which is equivalent to the film layer growing into the glass body. This preparation method can adapt to glass of different shapes.

[0064] In one embodiment, a hydrophobic layer may be provided on the nano-scale film layer. The hydrophobic layer may be formed by evaporating perfluorosilane. The hydrophobic layer serves as a water-repellent protective layer with low surface energy, reduces the possibility of hydrolysis between the glass and water vapor in the atmosphere, avoids deterioration of the glass strength, and improves durability in use.

[0065] The present application also provides a terminal device, the terminal device comprising the above-mentioned glass cover plate. The terminal device includes but is not limited to a screen terminal device.

[0066] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for preparing anti-reflection glass, characterized in that: include: In the etching step, the pretreated glass is immersed in a hydrolyzed acidic solution containing sodium silicate, disodium ETDA and aluminum chloride to generate a nano-scale film layer on the surface of the glass, wherein the film layer has a plurality of nano-scale protrusions smaller than the wavelength of visible light.

2. The preparation method according to claim 1, characterized in that: The acidic solution contains 0.1-0.4 mol / L sodium silicate, 0.04-0.12 mol / L disodium ETDA, and 0.05-0.15 mol / L aluminum chloride.

3. The preparation method according to claim 2, characterized in that: The thickness of the film layer is 150nm-250nm.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the etching step, the temperature of the acid solution is first controlled at 80±5° C., and then the pretreated glass is immersed in the acid solution.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The glass immersed in the acid solution is vibrated, and the vibration frequency is not less than 60 Hz.

6. The preparation method according to claim 5, characterized in that: The glass immersed in the acidic solution generates periodic vibration in the form of a sine wave. When the amplitude of the periodic vibration is less than 4 mm, the etching time is controlled to be greater than 50 minutes. When the amplitude of the periodic vibration is greater than 4 mm, the etching time is controlled to be less than 50 minutes.

7. The preparation method according to any one of claims 1 to 3, characterized in that: The pretreated glass is immersed in the acidic solution at a uniform speed of 18 cm / min to 20 cm / min.

8. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation method further comprises a pretreatment step arranged before the etching step: Cleaning the glass using a glass cleaning agent; and A 0.015vt% by volume hydrofluoric acid aqueous solution is used for corrosive cleaning.

9. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation method further comprises a strengthening step arranged after the etching step: The etched glass is immersed in a molten salt containing sodium and potassium.

10. The preparation method according to claim 9, characterized in that: The preparation method further comprises a post-processing step after the strengthening step: A hydrophobic layer of perfluorosilane is evaporated on the etched glass surface.

11. A glass cover plate, characterized in that: include: Cover plate body; and A nano-scale film layer is formed on the outer surface of the cover body, and the film layer is formed by etching the cover body.

12. The glass cover plate according to claim 11, characterized in that: The etching process comprises: The pretreated glass is immersed in a hydrolysis acid solution containing sodium silicate, disodium ETDA and aluminum chloride to generate a nano-scale film layer on the surface of the glass. The film layer has a number of nano-scale protrusions smaller than the wavelength of visible light.

13. The glass cover plate according to claim 11, characterized in that: The membrane layer is also provided with a hydrophobic layer.

14. A terminal device, characterized in that: Comprising the glass cover plate as claimed in claim 11.

Citation Information

Patent Citations

  • Preparation method for anti-reflective glass

    CN102491649A

  • Glass thinning etching solution and preparation method thereof

    CN107235641A

  • Preparation method of glass surface porous structure

    CN108191254A

  • Method of preparing antireflection glass by etching of salt chemical reagents

    CN109081600A

  • Surface-treating agent

    CN110003701A